2006
DOI: 10.4049/jimmunol.176.4.2381
|View full text |Cite
|
Sign up to set email alerts
|

Position-Dependent Repression and Promotion of DQB1 Intron 3 Splicing by GGGG Motifs

Abstract: Alternative splicing of HLA-DQB1 exon 4 is allele-dependent and results in variable expression of soluble DQβ. We have recently shown that differential inclusion of this exon in mature transcripts is largely due to intron 3 variants in the branch point sequence (BPS) and polypyrimidine tract. To identify additional regulatory cis-elements that contribute to haplotype-specific splicing of DQB1, we systematically examined the effect of guanosine (G) repeats on intron 3 removal. We found that the GGG or GGGG repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 71 publications
0
31
0
Order By: Relevance
“…In contrast, mutations of the downstream 5Јss-proximal GGGG motif result in increased splicing, suggesting that in this case, the motif acts as a splicing silencer. It was found in this study that point mutations within the second and third G residues had the most effect on splicing enhancement, but similar mutations in the 5Јss-proximal GGGG silencer were not tested (15). In the case of the brain region-specific C1 cassette exon of the GRIN1 transcript, mutation of the central two G residues of the 5Ј-proximal GGGG motif was shown to inactivate the silencer activity, but the effect of mutating only the first or fourth G residues of the GGGG motif was not tested (9).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, mutations of the downstream 5Јss-proximal GGGG motif result in increased splicing, suggesting that in this case, the motif acts as a splicing silencer. It was found in this study that point mutations within the second and third G residues had the most effect on splicing enhancement, but similar mutations in the 5Јss-proximal GGGG silencer were not tested (15). In the case of the brain region-specific C1 cassette exon of the GRIN1 transcript, mutation of the central two G residues of the 5Ј-proximal GGGG motif was shown to inactivate the silencer activity, but the effect of mutating only the first or fourth G residues of the GGGG motif was not tested (9).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that a GGGG motif proximal to the 5Јss of the brain region-specific C1 cassette exon of the N-methyl-Daspartic acid (NMDA)-type glutamate receptor NR1 subunit (GRIN1) transcript acts to silence inclusion of the C1 exon (9). Several GGGG motifs in the intron sequences upstream and downstream of alternative exon 4 of the HLA-DQB1 gene play a role in the differential inclusion of exon 3 into mRNA (15). In the HIV-1 genome, there is a GGGG motif which overlaps the last base of the U1 snRNP binding site and is just proximal to the 5Јss D2 sequence.…”
Section: Down Mutations Of 5ss D2 Decrease Exon 2 Inclusion and Levelmentioning
confidence: 99%
“…It has also been shown that intronic G triplets located immediately downstream of 5′ ss directly interact with U1 snRNA facilitating splice site recognition and functioning as ISE (87). On the other hand, G quadruplets adjacent to the 5′ ss have been shown to promote silencing of a brain-region-specific exon 19 of the GRIN1 gene (65) and inhibit the splicing of intron 3 in DQB1 reporter construct (88). Interestingly, the GGG/gu sequence similar to the one created by 54G was found to be inhibitory for NF1 exon 3 inclusion (89).…”
Section: Discussionmentioning
confidence: 99%
“…These sequences have the ability to form highly stable quadruplex structures (G-quartet) and are involved in many different biological processes, including alternative splicing, particularly when they are associated with 5 0 ss with intermediate scores [Xiao et al, 2009]. Several hnRNPs proteins, including hnRNP H but also hnRNP A1, A2, and F have also been shown to bind G-rich RNA sequences and to regulate splicing both positively and negatively in a position dependent manner [Buratti et al, 2004;Kralovicova and Vorechovsky, 2006]. Whether these sequences play a role in the context of the USH1C c.121016T4G and USH2A c.14582139C4T mutations would require further investigations.…”
Section: Activation Of Cryptic or De Novo 5 0 Ssmentioning
confidence: 99%